QRS complex and T wave planarity for the efficacy prediction of automatic implantable defibrillators - Hnatkova, Katerina; Andršová, Irena; Novotný, Tomáš; Vanderberk, Bert; Sprenkeler, David; Junttila, Juhani; Reichlin, Tobias; Schlögl, Simon; Vos, Marc A; Friede, Tim; Bauer, Axel; Huikuri, Heikki V; et al. (Heart (British Cardiac Society), 2024)
OBJECTIVE: To test the hypothesis that in recipients of primary prophylactic implantable cardioverter-defibrillators (ICDs), the non-planarity of ECG vector loops predicts (a) deaths despite ICD protection and (b) appropriate ICD shocks. METHODS: Digital pre-implant ECGs were collected in 1948 ICD recipients: 21.4% females, median age 65 years, 61.5% ischaemic heart disease (IHD). QRS and T wave three-dimensional loops were constructed using singular value decomposition that allowed to measure the vector loop planarity. The non-planarity, that is, the twist of the three-dimensional loops out of a single plane, was related to all-cause mortality (n=294; 15.3% females; 68.7% IHD) and appropriate ICD shocks (n=162; 10.5% females; 87.7% IHD) during 5-year follow-up after device implantation. Using multivariable Cox regression, the predictive power of QRS and T wave non-planarity was compared with that of age, heart rate, left ventricular ejection fraction, QRS duration, spatial QRS-T angle, QTc interval and T-peak to T-end interval. RESULTS: QRS non-planarity was significantly (p<0.001) associated with follow-up deaths despite ICD protection with HR of 1.339 (95% CI 1.165 to 1.540) but was only univariably associated with appropriate ICD shocks. Non-planarity of the T wave loop was the only ECG-derived index significantly (p<0.001) associated with appropriate ICD shocks with multivariable Cox regression HR of 1.364 (1.180 to 1.576) but was not associated with follow-up mortality. CONCLUSIONS: The analysed data suggest that QRS and T wave non-planarity might offer distinction between patients who are at greater risk of death despite ICD protection and those who are likely to use the defibrillator protection.
Keywords: Stroke Volume; Ventricular Function, Left; Electrocardiography; Male; funkce levé komory srdeční; Coronary Artery Disease; Risk Factors; Biomarkers; Death, Sudden, Cardiac; Aged; náhlá srdeční smrt; mužské pohlaví; senioři; tepový objem; srdeční arytmie; Defibrillators, Implantable; Arrhythmias, Cardiac; nemoci koronárních tepen; Myocardial Ischemia; lidé; ženské pohlaví; Humans; defibrilátory implantabilní; rizikové faktory; ischemická choroba srdeční; Female; elektrokardiografie